Trends in the incidence of attention deficit hyperactivity disorder in children and early risk factors - Leppänen, Marika; Vuori, Miika; Pape, Bernd; Kaittila, Anniina; Kraav, Siiri‐Liisi; Tolmunen, Tommi; Anis, Merja; Karukivi, Max; Rautava, Päivi. (Wiley, 2026)
Background
Few studies have used nationwide registry data from both primary and secondary healthcare services to examine the incidence of attention-deficit/hyperactivity disorder (ADHD) in children while accounting for early risk factors. We aimed to investigate trends in ADHD diagnoses and associated risk factors.
Methods
This study utilized data from population-based registers, comprising children born between 2001 and 2006 (N = 341,632), with follow-up data available up to age 12. Children who died perinatally, those with unclear or very low (<32 weeks) gestational age, as well as those with severe congenital syndromes or severe or unclear cognitive impairments were excluded. The main outcome was the cumulative incidence of ADHD, defined by ICD-10 codes F90, F90.0, F90.1, F90.8, F90.9, or F98.8. This outcome was adjusted for gestational age, sex, birth cohort, and maternal psychosocial factors during the child's first 3 years.
Results
The cumulative incidence of ADHD diagnosis at 0–12 years was 4.0% (3.9−4.0%) for the entire study (N = 324,766), 6.4% (6.2−6.5%) for boys, and 1.5% (1.5−1.6%) for girls. An ADHD diagnosis was more likely (adjusted odds ratios [95% confidence intervals]) among boys (4.6 [4.3–4.8]) and moderately preterm children (1.3 [1.2–1.4]), as well as in cases where the mother smoked during pregnancy (2.0 [1.9–2.1]), had a psychiatric disorder (2.0 [1.9–2.1]), or lived alone (1.4 [1.3–1.5]), compared to opposite condition. The cumulative incidence of ADHD diagnoses increased over time in both primary and secondary healthcare settings. There was a slight increase in the number of mothers diagnosed with any psychiatric disorder across cohorts, p < 0.0001.
Conclusion
The cumulative incidence of ADHD diagnoses in healthcare has been increasing. While psychosocial risk factors are associated with an elevated risk of receiving an ADHD diagnosis, other factors may also contribute to the rising diagnostic rates.